Automatic Game Design via Mechanic Generation - Zook, Alexander; Riedl, Mark (Proceedings of the AAAI Conference on Artificial Intelligence, 2014)
Game designs often center on the game mechanics - rules governing the logical evolution of the game. We seek to develop an intelligent system that generates computer games. As first steps towards this goal we present a composable and cross-domain representation for game mechanics that draws from AI planning action representations. We use a constraint solver to generate mechanics subject to design requirements on the form of those mechanics - what they do in the game. A planner takes a set of generated mechanics and tests whether those mechanics meet playability requirements - controlling how mechanics function in a game to affect player behavior. We demonstrate our system by modeling and generating mechanics in a role-playing game, platformer game, and combined role-playing-platformer game.